RESEARCH COMPETENCE OF HIGHER EDUCATION TEACHER: PROGRAM OF DEVELOPMENT - Sysoieva, Svitlana; Kozak, Luydmila (Continuing Professional Education: Theory and Practice, 2019)
Research competence is seen here as an integrated personal and professional quality of an expert, which reflects the motivation for scientific research, level of methodology of teaching research, personal qualities of as a researcher, in particular such as innovative thinking, the capacity for creativity and innovation. In the article authors grounded reasonable structure of research competence of higher education teacher (components: motivational and valuable, cognitive, procedural and active, informational and communicative, personal and creative, professional and reflexive). The artile presents meaningful description of each component of the research competence of higher education teacher for a sufficient level of its manifestation. The authors study the content of educational training programs of the faculty of the University aimed at developing research competence of the teacher (research module). Here is viewed goals, objectives, features of educational programmes, approaches to its implementation, structure and semantic research component module. Besides, the article presentes forms of teaching and learning to ensure the development of research competence of higher education teacher. While studying the research module is focused on mastering the teachers’ knowledge of the content, structure and criteria of formation of research competence of higher education teacher, the mastery of pedagogical research methodology, statistical analysis skills and presentation of results of pedagogical research, organization of educational and research for students of different educational levels.